FAKTOR KUNCI PENGEMBANGAN BIOETANOL AREN DI KABUPATEN BOALEMO PROVINSI GORONTALO - -, Ritabulan; Hiola, Abdul Samad (Universitas Gorontalo, 2018)
The potential of sugar palm spreading in Boalemo Regency strongly supports the development of paletan bioethanol in this area. However, these efforts face several interrelated and complex problems. This research aims to determine the key factors that influence the success of bioethanol development in Boalemo Regency, Gorontalo Province. This research uses Interpretative Structural Modeling (ISM) approach. The results of the analysis indicate that the key factors of bioethanol development in Boalemo Regency consist of: (i) development objective, which is to increase community's income; (ii) development needs, namely; availability of raw materials and human resources; (iii) the institutions involved, ie UPTD KPHP V Boalemo and KLHK Research, Development and Innovation Center; (iv) obstacles in development, namely regulatory / regulatory constraints; and (v) indicators, namely the level of public income and the amount of bioethanol production